2019
DOI: 10.1002/polb.24901
|View full text |Cite
|
Sign up to set email alerts
|

Directional Self‐Assembly of Fluorinated Star Block Polymer Thin Films Using Mixed Solvent Vapor Annealing

Abstract: We demonstrate the directional alignment of perpendicular‐lamellae domains in fluorinated three‐armed star block polymer (BP) thin films using solvent vapor annealing with shear stress. The control of orientation and alignment was accomplished without any substrate surface modification. Additionally, three‐armed star poly(methyl methacrylate‐block‐styrene) [PMMA‐PS] and poly(octafluoropentyl methacrylate‐block‐styrene) were compared to their linear analogues to examine the impact of fluorine content and star a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 88 publications
(158 reference statements)
0
8
0
Order By: Relevance
“…For instance, the Epps group demonstrated that solvent vapor annealing with soft shear could be used to produce long-range order for star block polymers with large Flory−Huggins interaction parameters, but achieving the desired nanostructure required carefully chosen solvent mixtures. 41 Another challenge relates to the large parameter spaces involved in block polymer self-assembly. Methods to form a target morphology are impacted by a number of factors, including block chemistry, substrate choice, film deposition method, and film thickness.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…For instance, the Epps group demonstrated that solvent vapor annealing with soft shear could be used to produce long-range order for star block polymers with large Flory−Huggins interaction parameters, but achieving the desired nanostructure required carefully chosen solvent mixtures. 41 Another challenge relates to the large parameter spaces involved in block polymer self-assembly. Methods to form a target morphology are impacted by a number of factors, including block chemistry, substrate choice, film deposition method, and film thickness.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, equipment can operate as fast as 15 m/s, and nanofabrication techniques that can reach this speed could be transformative. , Furthermore, new and existing approaches need to be demonstrated with application-relevant systems; the effectiveness of these methods cannot be assumed for all polymers, especially because macromolecular characteristics of the systems (e.g., ultrahigh molecular weight or large Flory–Huggins interaction parameters) can impact critical considerations like ordering kinetics. For instance, the Epps group demonstrated that solvent vapor annealing with soft shear could be used to produce long-range order for star block polymers with large Flory–Huggins interaction parameters, but achieving the desired nanostructure required carefully chosen solvent mixtures …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations